A Two-Moment Approximation for the Mean Waiting Time in the GI/G/s Queue - Kimura, Toshikazu (Management Science, 1986)
We provide a simple two-moment approximation formula for the mean waiting time in a GI/G/s queue. This formula has the form of a certain combination of the exact mean waiting times for the D/M/s, M/D/s and M/M/s queues, and hence it can be easily calculated by using some queueing tables. The quality of the approximation is tested by comparing it with known solutions in particular cases.